2019
DOI: 10.1590/1983-21252019v32n330rc
|View full text |Cite
|
Sign up to set email alerts
|

Carotene Yield in Sweet Potato After Potassium and Phosphorus Fertiliser Application

Abstract: Sweet potato is one of the most important foods in the world. Among the different cultivated genotypes, it is worth highlighting those with orange pulp due to their ability to supply adequate amounts of provitamin A carotenoids to humans. This study evaluates the effect of potassium and phosphorus fertiliser application on carotenoid yield in sweet potatoes. Two experiments were carried out in São Luis City, Maranhão State, Brazil. The experimental design was a randomised block design, with six treatments for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The application of 240 and 183 kg ha −1 K 2 O divided between plantings plus 3 MP also provided yields similar to treatments with three K application times, and the response to K application rates was greater when the K application was split. When K application occurred exclusively at planting, other studies also reported a lower response of sweetpotatoes to K rates in K‐deficient soils (Cecílio Filho et al., 2016; Nascimento et al., 2019). According to Nogueira et al.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The application of 240 and 183 kg ha −1 K 2 O divided between plantings plus 3 MP also provided yields similar to treatments with three K application times, and the response to K application rates was greater when the K application was split. When K application occurred exclusively at planting, other studies also reported a lower response of sweetpotatoes to K rates in K‐deficient soils (Cecílio Filho et al., 2016; Nascimento et al., 2019). According to Nogueira et al.…”
Section: Discussionmentioning
confidence: 97%
“…Brazilian guidelines for sweetpotato fertilization in K‐deficient soils recommend K application rates between 90 and 120 kg ha −1 K 2 O (Casali, 1999; Echer et al., 2015; Lorenzi et al., 1997; Silva et al., 2002). However, in Brazilian K‐deficient soils, positive productive responses of sweetpotatoes were observed up to 85 kg ha −1 K 2 O when K fertilizer was applied exclusively at planting (Cecílio Filho et al., 2016; Nascimento et al., 2019), and positive responses were observed up to 174–180 kg ha −1 K 2 O when K was split applied (Brito et al., 2006; Nogueira et al., 1992). However, in the case of K‐deficient soils, our results showed that if K fertilization was split applied three times, the total and marketable sweetpotato root yield increased up to 153 and 179 kg ha −1 K 2 O, respectively, with no further response to higher K application rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of P doses can be explained by the fact that phosphorus is a component of pyrophosphates, which are essential intermediate constituents in the biosynthesis of carotenoids important for the color of fruits, causing an increase in carotenoid content (Li et al, 2022). Nascimento et al (2019) observed that P influenced the content of total carotenoids in the Beauregard sweet potato cultivar, with a recommended P 2 O 5 dose of 174.09 kg ha -1 . Cordeiro et al (2023) mentioned that soils with P concentration < 5.0 mg dm -3 require 68 kg ha -1 of P for maximum production of sweet potato, showing similarity for some variables in the present study, since the P concentrations here were 4.20 and 2.37 mg dm -3 , respectively, for depths of 0-0.20 m and 0.20-0.40 m, that is, P < 5.0 mg dm -3 .…”
Section: /7mentioning
confidence: 99%
“…Potassium acts as an activator throughout the whole life cycle of sweet potatoes [9]. Especially for various enzymes in sweet potatoes, potassium can improve the photosynthesis ability of sweet potato leaves, the transportation of light and products, the plant's resistance to adversity, and the plant's resistance and tolerance to adverse environments [10]. Potassium is also used as a lubricant for carbohydrate transfer and distribution between sink and source organs of crops.…”
Section: Introductionmentioning
confidence: 99%